Field Test and Numerical Simulation Study on Pipe Sticking of Pipe Jacking in Composite Stratum - Shilei Zhang; Xiaodong Xu; Feilun Luo; Tao Shi; Tianshuo Xu; Peng Zhang (Buildings)
In this study, the jacking force of a stuck pipe was explored under various contact conditions in long-distance composite strata. The Jiaoliu River jacking project in Yichao, Inner Mongolia, was selected for study, and the precise location of the pipe sticking was determined by laying strain gauges on the surface of the pipe and via integration with the measured data. Corresponding technical measures for releasing the pipe sticking were also put forward. Finally, ABAQUS 2022 software was used to establish a finite element analysis model of jacking force considering full contact conditions, and the maximum friction coefficient of the pipe that can be jacked forward in the pipe sticking state was calculated, providing a reference for related engineering cases. The results show that the position of the pipe sticking can be accurately identified through strain gauges on the surface of the pipe. The axial jacking force is transmitted more effectively in the upper section of the pipe than in the lower section, and as the jacking force increases, the length of the pipe becomes longer according to this rule. Measures were taken to adequately lubricate the pipe affected by sticking to ameliorate this condition.